Coetzee and Borges: the Southern Connections - Galvan-Alvarez, Enrique; Galván, Fernando (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2023)
This essay addresses some of the relations that can be traced between, on the one hand, J. M. Coetzee and Jorge Luis Borges and, on the other, the concept of the Global South and Coetzee’s recent approach to Latin America. The development of his ideas about the notion of the South or “real South,” as opposed to the “mythic South,” is discussed and illustrated through a brief analysis of Borges’s tale “El Sur” [“The South”] and Coetzee’s novel Disgrace. These two texts help us in focusing Coetzee’s rejection of the so-called “Northern Gaze,” a Westernised world-view dominated by the English language, and his preference for Spanish as the language for the initial publication of his latest books.